The strange semipresidential system: Between myth and reality, is it suitable for Chile? - Lagos Torres, Alejandro (Derecho Público Iberoamericano, 2020)
The semi-presidential system is analyzed, seeking to characterize it based on experience, but with a different perspective that authors of the 20th century. Government systems of countries classified as semipresidential and of countries that have attempted reforms to mitigate hyper-presidentialism are studied, trying to determine whether the semipresidential system is suitable for Chile.